Designing Gender-Specific Toilet and Urinal Needs Calculation Templates for Rural and Urban Schools: Lessons from the Republic of Benin - TOSSOU, COCOU RIGOBERT; KOUEVI, TEKO AUGUSTIN (My University, 2024)
Gender equity, quality education, and sanitation in rural and urban areas are widely considered development imperatives. Therefore, many developed countries have scientifically and technically developed norms for the calculation and the design of toilet and urinal needs of their students, which is not yet the case in most developing countries, including the Republic of Benin, that lack socio-culturally adapted gender-specific toilets and urinal needs calculation and design norms. This paper fills this scientific and genderspecific norms gap, by discussing the process and the results of the design of school toilet and urinal needs calculation templates and norms in the Republic of Benin. The study that led to this design took place between June 2013 and October 2015 and consisted mainly of observing and recording defecation and urination needs satisfaction in toilets and open spaces by 8,160 female and 13,263 male students of 13 schools purposively selected in four agroecological and sociocultural areas of Benin. The main data recorded related, among other data, to the start and end times of the use of the toilets and open spaces; the needs satisfied; the peak times and durations of breaks and of toilet needs satisfaction; the numbers of female and male students and non-students who use and who can potentially use the toilets and urinals. These raw data were processed to infer and calculate eight parameters used in each template. This process led to the design of eight area-, gender-, and disability-specific templates and norms in use since 2016, in the target areas. Further studies will assess and report on the performance of these templates and norms.
Keywords: Agroecology; Culture; Gender equity; Secondary schools; Toilet and urinal needs’ calculation templates; West Africa